1991
DOI: 10.1002/j.1460-2075.1991.tb04892.x
|View full text |Cite
|
Sign up to set email alerts
|

Plastid translation and transcription genes in a non-photosynthetic plant: intact, missing and pseudo genes.

Abstract: The non‐photosynthetic, parasitic flowering plant Epifagus virginiana has recently been shown to contain a grossly reduced plastid genome that has lost many photosynthetic and chloro‐respiratory genes. We have cloned and sequenced a 3.9 kb domain of plastid DNA from Epifagus to investigate the patterns of evolutionary change in such a reduced genome and to determine which genes are still present and likely to be functional. This 3.9 kb domain is colinear with a 35.4 kb region of tobacco chloroplast DNA, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(94 citation statements)
references
References 53 publications
5
88
1
Order By: Relevance
“…In addition to PEP, the existence of NEP has already been suggested from studies with the parasite Epifagus virginiana, which lacks the plastid rpoBC operon (Morden et al, 1991). Similar results were obtained for the plastid ribosomedeficient barley (Hordeum vulgare) mutant albostrians (Hess et al, 1993) and tobacco (Nicotiana tabacum) rpo deletion mutants (Allison et al, 1996;Hajdukiewicz et al, 1997), both still synthesizing plastid transcripts.…”
Section: Introductionsupporting
confidence: 71%
“…In addition to PEP, the existence of NEP has already been suggested from studies with the parasite Epifagus virginiana, which lacks the plastid rpoBC operon (Morden et al, 1991). Similar results were obtained for the plastid ribosomedeficient barley (Hordeum vulgare) mutant albostrians (Hess et al, 1993) and tobacco (Nicotiana tabacum) rpo deletion mutants (Allison et al, 1996;Hajdukiewicz et al, 1997), both still synthesizing plastid transcripts.…”
Section: Introductionsupporting
confidence: 71%
“…Several appropriate primers were designed based on the sequences of Nicotiana tabacum (tobacco) 6) and Epifagus verginiana 7) so that whole region of the rps2 gene could be amplified (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the function of tRNA upstream sequences have shown that either they contain prokaryote-type promoters (Gruissem et al 1983;Steinmetz et al 1983;Wu et al 1997) or there are eukaryote-type internal promoters directly in the tRNA (Galli et al 1981;Gruissem et al 1986;Cheng et al 1997). The loss of promoter elements from the nonphotosynthetic Epifagus tRNA Glu (UUC) (Morden et al 1991) suggests, however, that prokaryote-type promoters are not always required for transcription of tRNA genes, and a few studies of tRNA transcription in lineages with functioning chloroplasts also suggest this (Gruissem et al 1986;Jahn 1992;Wu et al 1997). We therefore interpret the lack of promoter elements in the upstream regions of Gnetales tRNA Thr , tRNA Leu , and tRNA Phe genes as indicating that these genes have internal promoters, relieving their spacer regions from functional constraints that would come from harboring functional promoters.…”
Section: Behavior Of the Trnl Intron And Adjacent Spacers In Gnetummentioning
confidence: 99%